SGLT-2 inhibitors and cardiovascular outcomes in patients with and without a history of heart failure: a systematic review and meta-analysis. Issue 6 (11th January 2022) - Razuk, Victor; Chiarito, Mauro; Cao, Davide; Nicolas, Johny; Pivato, Carlo A; Camaj, Anton; Power, David; Beerkens, Frans; Jones, Davis; Alter, Aviv; Mathew, Alvin; Spirito, Alessandro; et al.
Abstract: Aims: Sodium–glucose cotransporter 2 (SGLT-2) inhibitors have cardiovascular (CV) benefits in patients with heart failure with reduced ejection fraction (HFrEF). Whether these medications improve CV outcomes irrespective of heart failure history or left ventricular ejection fraction (LVEF) in HFrEF remains unknown. Methods and results: All randomized, placebo-controlled trials of SGLT-2 inhibitors reporting similar CV outcomes were searched in PubMed from 1 January 2010 to 1 October 2021. The primary outcome was the composite of hospitalization for heart failure or CV death. Secondary outcomes included all-cause mortality. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were used as effect estimates and calculated with a random-effects model. Data from 11 trials and a total of 66 957 patients ( n = 36 758 SGLT-2 group, n = 30 199 placebo group) were included. SGLT-2 inhibitors reduced the risk of hospitalization for heart failure or CV death in patients with (HR 0.76, 95% CI 0.71–0.80) and without (HR 0.76, 95% CI 0.68–0.86; P interaction = 0.69) heart failure. Patients with (HR 0.87, 95% CI 0.80–0.95) and without (HR 0.84, 95% CI 0.73–0.95; P interaction = 0.67) heart failure treated with SGLT-2 inhibitors had a reduction in all-cause mortality. Reduction in the primary outcome was consistently observed in HFrEF patients with (HR 0.68, 95% CI 0.59–0.78) and without (HR 0.84, 95% CI 0.71–0.99; P interaction = 0.13) severely reduced LVEF, and in heart failure with preserved ejection fraction patients (HR 0.80, 95% CI 0.70–0.92; P interaction = 0.65). Conclusion: SGLT-2 inhibitors improved CV outcomes irrespective of heart failure history or type, and severity of LVEF reduction.